Factors Affecting Concrete Recycling Adoption in the Construction Projects - Badraddin, A. K.; Abdul Rahimi, Abdul Rahman; Zahrizan, Zakaria; Muzamir, Hasan (Universiti Malaysia Pahang, 2021)
Recycling addresses environmental issues associated with solid waste by minimizing overall resource consumption and environmental impact. In the construction industry, concrete recycling is crucial because concrete is the most dominant waste of construction and demolition waste. However, its implementation is at a low level in numerous countries becauseconstruction managers refuse to adopt concrete recycling in practice. This study's objective is to identify factors that are affecting decisions in adopting concrete recycling from the constructionmanagers' perspective. To achieve this objective, open-ended interview data with constructionmanagers are analyzed. Eleven factors affecting decisions in adopting concrete recycling inure identified. The factors are recycling factories, availability of raw material, quality, cost, reliable standard, government encouragement, legally, acceptance factor, proper planning, skilled workforce, and management. This research contributes to the body of knowledge in the analysis of factors that influence the acceptance of concrete recycling from industry practitioners' perspectives, which could help researchers and industry practitioners develop strategies to reduce the rejection of concrete recycling among construction managers. The findings of this research would help improve the success of adopting concrete recycling in the construction industry.